The Relationship between The Use of Smartphone and Student Achievement in Class VIII - Della Widia Sari; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research is motivated by the low learning achievement of class VIII students at SMP Negeri 6 Lubuk Basung, this is forgotten because the use of smartphones in students is not good. This study aims to describe the use of smartphones in class VIII students, describe student achievement in class VIII, and see the relationship between smartphone use and student achievement in class VIII at SMP Negeri 6 Lubuk Basung. This type of research is quantitative with correlational descriptive technique. The population was all class VIII students and the sample was taken using a sampling technique, namely cluster random sampling. The data analysis technique uses the percentage formula and product moment correlation. The results showed that: the use of smartphones in students was classified as poor, student learning achievement was low, and there was a significant relationship between smartphone use and student achievement in class VIII. Furthermore, it is recommended for schools to apply strict rules regarding the use of smartphones in students so that they can affect student achievement. Hope for educators and parents to be able to monitor the use of smartphones on students to avoid negative things and decrease student achievement. For further researchers to see other variables related to student achievement.